2007
DOI: 10.1128/mcb.01234-06
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Protein Tyrosine Phosphatase, Distinctively Expressed in Activated-B-Cell-Like Diffuse Large B-Cell Lymphomas, Is the Nuclear Phosphatase of STAT6

Abstract: Diffuse large B-cell lymphomas (DLBCLs) consist of clinically distinct subtypes: germinal center B-cell (GCB)-like and activated-B-cell (ABC)-like tumors, characterized by long and short survival, respectively. We reported distinct interleukin 4 (IL-4) responsiveness and STAT6 signaling in these DLBCL subtypes. Increased nuclear dephosphorylation of phospho-STAT6 (pSTAT6) was observed in ABC-like tumors, which exhibited a different expression profile of protein tyrosine phosphatases (PTPs). Among the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 42 publications
3
74
3
Order By: Relevance
“…The Janus kinases JAK1 and JAK3 are dephosphorylated by PTPN2, resulting in modulation of IL-2, IFNγ, and IFNα signaling [54], while the transcription factors STAT1, STAT3, and STAT6 are targets of PTPN2 in response to IFNγ, IL-6, and IL-4, respectively [55][56][57]. TNF has been shown to stimulate PTPN2 interaction with the adaptor protein TNF receptor-associated factor 2 (TRAF2), with subsequent dephosphorylation of c-SRC and regulation of ERK activation [58].…”
Section: Known Function Of Ptpn2mentioning
confidence: 99%
“…The Janus kinases JAK1 and JAK3 are dephosphorylated by PTPN2, resulting in modulation of IL-2, IFNγ, and IFNα signaling [54], while the transcription factors STAT1, STAT3, and STAT6 are targets of PTPN2 in response to IFNγ, IL-6, and IL-4, respectively [55][56][57]. TNF has been shown to stimulate PTPN2 interaction with the adaptor protein TNF receptor-associated factor 2 (TRAF2), with subsequent dephosphorylation of c-SRC and regulation of ERK activation [58].…”
Section: Known Function Of Ptpn2mentioning
confidence: 99%
“…Previous work has shown that B cells from mice lacking STAT6 failed to produce significant amounts of IgE and IgG1 after infection with the nematode parasites (Raia et al, 2011;Turqueti-Neves et al, 2014). The binding sites of STAT6 have been found in the target regions of a variety of IL-4-mediated genes, including CD23 (Cooper et al, 2012), IL-4R (Jenkins et al, 2013), eotaxin-1 (Waddell et al, 2013), eotaxin-3 (Nakayama et al, 2010), FIZZ1 (Dasgupta et al, 2011), and in Ig germline e (Lu et al, 2007) promoters. Recently, IL-4-driven STAT6 constitutive activation has been found in various diseases, such as allergy (Hong et al, 2014), tumors (Cheah et al, 2014;Creytens et al, in press;Koelsche et al, 2014), and lymphoproliferative disorders (Rawal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Since PTPN2 represents a phosphatase for both JAKs and STATs, and since PTPN2 was found to be mutated in HL cell line, we investigated whether mutation of PTPN2 could be responsible for the deregulation of the JAK/STAT signaling cascade in HL. 8,18 We selected a cohort of HL samples (10 nodular lymphocyte-predominant HL, 27 nodular sclerosis cHL, 6 mixedcellularity cHL, 5 lymphocyte-rich cHL, and 2 lymphocyte-depleted cHL) for a comprehensive sequence analysis of the coding region of PTPN2 using the 454 amplicon deep sequencing technology (Roche 454 GS-FLX). This technology was chosen because HL samples usually carry only a very low percentage of clonal Hodgkin's and Reed Sternberg cells; typically less than 1%.…”
Section: Sequence Analysis Of Ptpn2 In Hl and T-nhlmentioning
confidence: 99%